Familial co-aggregation and shared genetics of cardiometabolic disorders and traits: data from the multi-generational Lifelines Cohort Study - Triatin, Rima D.; Chen, Zekai; Ani, Alireza; Wang, Rujia; Hartman, Catharina A.; Nolte, Ilja M.; Thio, Chris H. L.; Snieder, Harold (Cardiovascular diabetology, 2023)
Background It is unclear to what extent genetics explain the familial clustering and the co-occurrence of distinct cardiometabolic disorders in the general population. We therefore aimed to quantify the familial (co-)aggregation of various cardiometabolic disorders and to estimate the heritability of cardiometabolic traits and their genetic correlations using the large, multi-generational Lifelines Cohort Study. Methods We used baseline data of 162,416 participants from Lifelines. Cardiometabolic disorders including type 2 diabetes (T2D), cardiovascular diseases, hypertension, obesity, hypercholesterolemia, and metabolic syndrome (MetS), were defined in adult participants. Fifteen additional cardiometabolic traits indexing obesity, blood pressure, inflammation, glucose regulation, and lipid levels were measured in all included participants. Recurrence risk ratios (λ R ) for first-degree relatives (FDR) indexed familial (co-)aggregation of cardiometabolic disorders using modified conditional Cox proportional hazards models and were compared to those of spouses. Heritability (h 2 ), shared environment, and genetic correlation (r g ) were estimated using restricted maximum likelihood variance decomposition methods, adjusted for age, age 2 , and sex. Results Individuals with a first-degree relative with a cardiometabolic disorder had a higher risk of the same disorder, ranging from λ FDR of 1.23 (95% CI 1.20–1.25) for hypertension to λ FDR of 2.48 (95% CI 2.15–2.86) for T2D. Most of these were higher than in spouses (λ Spouses < λ FDR ), except for obesity which was slightly higher in spouses. We found moderate heritability for cardiometabolic traits (from h 2 CRP : 0.26 to h 2 HDL : 0.50). Cardiometabolic disorders showed positive familial co-aggregation, particularly between T2D, MetS, and obesity (from λ FDR obesity-MetS : 1.28 (95% CI 1.24–1.32) to λ FDR MetS-T2D : 1.61 (95% CI 1.52–1.70)), consistent with the genetic correlations between continuous intermediate traits (ranging from r g HDL-Triglycerides : − 0.53 to r g LDL-Apolipoprotein B : 0.94). Conclusions There is positive familial (co-)aggregation of cardiometabolic disorder, moderate heritability of intermediate traits, and moderate genetic correlations between traits. These results indicate that shared genetics and common genetic architecture contribute to cardiometabolic disease.